The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content